Epidemiologia das hepatites B, D e E no Noroeste de Mato Grosso - Ferreira Junior, Paulo Antonio (2023)
Hepatitis B virus (HBV) infection occurs mainly in developing countries. In Brazil, the Western Amazon has the highest prevalence rates in the country. It is also the only Brazilian region where HBV co-infection with hepatitis D virus (HDV) occurs. Objective: To estimate the prevalence of HBV and HDV infections in a municipality in the northwest of Mato Grosso, in the Western Amazon, and to assess the impact of vaccination on the endemic levels of these infections. Methods: A sero-epidemiological survey for markers of hepatitis B and D was carried out to obtain demographic, socioeconomic and risk factor data for sexually and parenterally transmitted diseases in the district of Três Fronteiras, which borders Mato Grosso, Rondônia and Amazonas. The markers were analyzed using the ELISA technique. Statistical significance for all the analyses was set at a probability level of 0.05. Results: The study took place in July 2012 and was re-evaluated in July 2013. It included 623 individuals from a total of 125 households in the district. Sanitation conditions and access to services were extremely precarious in the community, characterized by inadequate infrastructure and a limited supply of basic resources. This precariousness was manifested through sanitation systems that were insufficient to meet the needs of the population, and a lack of access to essential services. Of the individuals included in the study, 421 (67.6%) were male. The average age was 30.9 years with a Standard Deviation (SD) of 15.8. Only 275 (44.1%) individuals reported having been vaccinated for hepatitis B. 51 (8.2%) had experienced jaundice throughout their lives and 21 (3.4%) had received a blood transfusion. Of the 623 individuals studied, 219 (35.2%) were anti-HBc positive, characterizing previous or current HBV infection. There was no association between this marker and any of the variables studied. Conclusion: The community studied had a low intermediate endemicity of HBV infection.